Measurements of condensation nuclei in the Airborne Arctic Stratospheric Expedition - Observations of particle production in the polar vortex - Wilson, J. C.; Stolzenburg, M. R.; Clark, W. E.; Loewenstein, M.; Ferry, G. V.; Chan, K. R. (1990)
The ER-2 Condensation Nucleus Counter (ER-2 CNC) was operated in the Airborne Arctic Stratospheric Expedition (AASE) in January and February 1989. The ER-2 CNC measures the mixing ratio of particles, CN, with diameters from approximately 0.02 to approximately 1 micron. The spatial distribution of CN in the Arctic polar vortex was found to resemble that measured in the Antarctic in the Spring of 1987. The vertical profile of CN in the vortex was lowered by subsidence. At altitudes above the minimum in the CN mixing ratio profile, CN mixing ratios correlated negatively with that of N2O, demonstrating new particle production. CN serve as nuclei in the formation of Polar Stratospheric Clouds (PSCs) and the concentration of CN can affect PSC properties.